Escherichia coli attachment to model particulates: The effects of bacterial cell characteristics and particulate properties. - Xiao Liang; Chunyu Liao; Michelle L Soupir; Laura R Jarboe; Michael L Thompson; Philip M Dixon (PLoS ONE)
E. coli bacteria move in streams freely in a planktonic state or attached to suspended particulates. Attachment is a dynamic process, and the fraction of attached microorganisms is thought to be affected by both bacterial characteristics and particulate properties. In this study, we investigated how the properties of cell surfaces and stream particulates influence attachment. Attachment assays were conducted for 77 E. coli strains and three model particulates (ferrihydrite, Ca-montmorillonite, or corn stover) under environmentally relevant conditions. Surface area, particle size distribution, and total carbon content were determined for each type of particulate. Among the three particulates, attachment fractions to corn stover were significantly larger than the attachments to 2-line ferrihydrite (p-value = 0.0036) and Ca-montmorillonite (p-value = 0.022). Furthermore, attachment to Ca-montmorillonite and corn stover was successfully modeled by a Generalized Additive Model (GAM) using cell characteristics as predictor variables. The natural logarithm of the net charge on the bacterial surface had a significant, positive, and linear impact on the attachment of E. coli bacteria to Ca-montmorillonite (p-value = 0.013), but it did not significantly impact the attachment to corn stover (p-value = 0.36). The large diversities in cell characteristics among 77 E. coli strains, particulate properties, and attachment fractions clearly demonstrated the inadequacy of using a static parameter or linear coefficient to predict the attachment behavior of E. coli in stream water quality models.